2018
DOI: 10.24235/amwal.v10i1.2812
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Religiusitas dan Persepsi Nasabah terhadap Keputusan Memilih Bank Syariah

Abstract: AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh religiusitas dan persepsi para nasabah Perbankan Syariah dalam menentukan pilihan menjadi nasabah di BRI Syariah. Penelitian ini dilakukan untuk melihat seberapa besar pengaruh religiusitas dan persepsi terhadap keputusan memilih perbankan syariah di PT. BRI Syariah di Medan. Jenis penelitian ini adalah penelitian kausal dengan metode pengumpulan data menggunakan metode survey dan teknik pengumpulan data menggunakan teknik kuisioner serta sampel dipilih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 0 publications
5
15
0
10
Order By: Relevance
“…Based on studies from (Imran & Hendrawan, 2018) and (SAPUTRA & KHOIRUL ANWAR, 2019) that when perceptions about Islamic banks (perceptions of bank interest, and profit-sharing) increase, it will increase interest in choosing Islamic banks. This finding is in line with what was expressed by (Zuhirsyan & Nurlinda, 2018) that religiosity and perception simultaneously (together) have a positive impact on the decision to choose a sharia bank. Ethical perceptions will also impact the customer switching intention of Islamic Banks (Jannah & Arry Widodo, 2018).…”
Section: Literature Reviewsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on studies from (Imran & Hendrawan, 2018) and (SAPUTRA & KHOIRUL ANWAR, 2019) that when perceptions about Islamic banks (perceptions of bank interest, and profit-sharing) increase, it will increase interest in choosing Islamic banks. This finding is in line with what was expressed by (Zuhirsyan & Nurlinda, 2018) that religiosity and perception simultaneously (together) have a positive impact on the decision to choose a sharia bank. Ethical perceptions will also impact the customer switching intention of Islamic Banks (Jannah & Arry Widodo, 2018).…”
Section: Literature Reviewsupporting
confidence: 92%
“…Customer religiosity does play an essential role in the decision process for customers to choose Islamic banks. According to (Zuhirsyan & Nurlinda, 2018), partially religiosity is more influential on the decision to choose a sharia bank than perception. In the case in Afghanistan (Safi et al, 2020) found that customer choice of Islamic bank products is influenced by the variable of religiosity (religious belief).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Religiosity, which is a religious act in a person related to the banking world, namely avoiding usury, is considered capable of influencing the decision to become a customer. This is supported by previous research conducted by (Zuhirsyan & Nurlinda, 2018). A previous study states that promotional factors greatly influence making customer decisions to save at Islamic banks (Hasanuddin, SS, & Nofrianto, 2019).…”
Section: Introductionsupporting
confidence: 75%
“…Religiosity is the act of someone related to the wider community in developing creative devotion to God. A religiosity is a form of complete integration between religious knowledge, feelings, and religious actions within a person (Zuhirsyan& Nurlinda, 2018). A religiosity is also a form of belief in believing in one's religion by practicing and obeying all the rules contained therein and doing things related to worship happily without coercion.…”
Section: Religiositymentioning
confidence: 99%
See 1 more Smart Citation